Conhecimento de populações tradicionais como possibilidade de conservação da natureza: uma reflexão sobre a perspectiva da etnoconservação - Bárbara Elisa Pereira; Antonio Carlos Diegues (Desenvolvimento e Meio Ambiente, 2010)
The global environmental situation has been a concern of several segments of society. Within this scenario,new conceptions have been adopted in order to reach an effective environmental protection, resulting inwide discussions in different political spheres, from local to global levels. These issues include indigenouspeople and their respective knowledge, discussed through a new approach called ethno conservation,which aims at associating environmental conservation with indigenous knowledge and management of natural resources. Ethno conservation is an area of expertise from ethno science, based in elements oflanguage, culture and biology, in order to understand the meaning and classification of natural resources.As ethno conservation is strongly related with indigenous people and their knowledge there is a needto take these aspects into consideration, in order to understand the contribution of this new approach toenvironmental conservation.